A Novel High Gain Monopole Antenna Array for 60 GHz Millimeter-Wave Communications - Tarek S. Mneesy; Radwa K. Hamad; Amira I. Zaki; Wael A. E. Ali (Applied Sciences, 2020)
This paper presented the design and implementation of a 60 GHz single element monopole antenna as well as a two-element array made of two 60 GHz monopole antennas. The proposed antenna array was used for 5G applications with radiation characteristics that conformed to the requirements of wireless communication systems. The proposed single element was designed and optimized to work at 60 GHz with a bandwidth of 6.6 GHz (57.2–63.8 GHz) and a maximum gain of 11.6 dB. The design was optimized by double T-shaped structures that were added in the rectangular slots, as well as two external stubs in order to achieve a highly directed radiation pattern. Moreover, ring and circular slots were made in the partial ground plane at an optimized distance as a defected ground structure (DGS) to improve the impedance bandwidth in the desired band. The two-element array was fed by a feed network, thus improving both the impedance bandwidth and gain. The single element and array were fabricated, and the measured and simulated results mimicked each other in both return loss and antenna gain.